Factors influencing utilization of cervical cancer screening services among married women in community, Chitwan - Ranabhat, Mina Kumari; Thapa, Basanta (Journal of Chitwan Medical College, 2017)
Cervical cancer is one of the most prevalent cancers affecting women globally. It is the fourth most common cancer in women and the seventh overall. The morbidity and mortality of cervical cancer can be highly reduced through vaccination against human papilloma virus, regular screening and timely intervention. The objective of this study was to find out the factors influencing utilization of cervical cancer screening services among married women aged 30-60 of Bharatpur Sub-Metropolitan 19, Chitwan. A community based descriptive cross sectional research design was used, 175 married women were selected using simple random sampling technique. Semi- structured interview schedule was used to collect the data within four weeks. The collected data was entered in Epi data 3.1 and exported to IBM SPSS version 20. Out of 175 women, 42.3% of the respondents were of 30-39 years, 72% were literate, 18.9% had good level of awareness of cervical cancer screening, 44% had utilized cervical cancer screening services and 77.9% of the respondents had done screening only one time. The association showed between utilization of cervical cancer screening services such as duration of marriage (p=0.025), involvement in cervical cancer awareness programme (p=<0.001), fear (p=0.007), shyness (p=<0.001), preference of sex of health personnel (p=0.016), time to reach nearest screening center (p=0.024) and need of cervical cancer screening without any problems of cervix (p=<0.001). Multivariate analysis showed that association between utilization of cervical cancer screening services such as duration of marriage 3.036 times, fear 2.992 times, shyness 3.335 times and need of cervical cancer screening without any problems of cervix 30.720 times more likely to utilize cervical cancer screening services.